Species limits in the Tawny-crowned Pygmy-tyrant Euscarthmus meloryphus complex (Aves: Passeriformes: Tyrannidae) - Franz, Ismael; Alvares, Diego Janisch; Borges-Martins, Márcio (Zootaxa, 2020)
Euscarthmus pygmy-tyrants include two species of tiny passerines that inhabit semi-open landscapes in South America. One of these, Euscarthmus meloryphus is a taxonomic complex comprising three recognized subspecies for which previously proposed splits and lumps were not founded on proper taxonomic analysis. We assessed morphology (morphometrics and plumage), distribution models, and vocalizations of a substantial dataset with the aim of evaluating species limits within the E. meloryphus complex. Our results support the recognition of two species, the widespread E. meloryphus from east-central South America, and E. fulviceps from Ecuador and Peru, which are clearly diagnosable on morphological and vocal characters. We consider that E. meloryphus paulus from Colombia and Venezuela is a synonym of the nominotypical taxon based on the absence of diagnostic vocal and morphological characters. The allopatric distribution of the two populations of E. meloryphus may be related to the savannah connections during the LGM in South America. Further, we show that Lepturus ruficeps Swainson, 1838 is a synonym of E. rufomarginatus instead of E. meloryphus as it has long been treated.